Pengaruh Environmental, Social, Dan Governance (ESG) Dan Leverage Terhadap Kinerja Keuangan Dengan Ukuran Perusahaan Sebagai Variabel Moderasi Pada Sektor Consumer Non Cyclicals - Fajriani Rahma Fitri; Berta Agus Petra; Putri Intan Permata Sari; Rindy Citra Dewi (Jurnal IAKP : Jurnal Inovasi Akuntansi Keuangan & Perpajakan, 2025)
This research aims to determine the effect of environmental, social, and governance (ESG) and leverage on financial performance with firm size as a moderating variable in the consumer non-cyclical sectors listed on the Indonesia Stock Exchange for the 2019-2023 period. This study uses a quantitative research method with a population of 33 companies out of 129 companies for the 2019-2023 period. The sampling method uses purposive sampling with criteria that have been determined by the researcher. This study uses secondary data. The data analysis method uses panel data regression analysis using Eviews 12 software.The results of the study show that environmental, social, and governance (ESG) and leverage have no effect on financial performance. Firm size as a moderating variable is unable to moderate environmental, social, and governance (ESG) on financial performance. However, firm size is able to moderate leverage on financial performance.